2016
DOI: 10.1021/acs.jpca.6b04138
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Optical, and Electronic Properties of Wide Bandgap Perovskites: Experimental and Theoretical Investigations

Abstract: Wide bandgap hybrid halide perovskites based on bromine and chlorine halide anions have emerged as potential candidates for various optoelectronic devices. However, these materials are relatively less explored than the iodine-based perovskites for microscopic details. We present experiment and first-principles calculations to understand the structural, optical, and electronic structure of wide bandgap CH3NH3Pb(Br1-xClx)3 (x = 0, 0.33, 0.66, and 1) 3D hybrid perovskite materials. We substituted Br(-) with Cl(-)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 44 publications
8
52
0
Order By: Relevance
“…Perovskites consisting of MAPbCl 3 , MAPbBr 3 , and MAPbI 3 have band‐gab energies of 3.1, 2.3, and 1.6 eV, respectively . These values come from the energy difference between (Pb)6s(X)np valence band maximum (VBM) and (Pb)6p conduction band minimum (CBM) orbitals with X=Cl, Br, or I …”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Perovskites consisting of MAPbCl 3 , MAPbBr 3 , and MAPbI 3 have band‐gab energies of 3.1, 2.3, and 1.6 eV, respectively . These values come from the energy difference between (Pb)6s(X)np valence band maximum (VBM) and (Pb)6p conduction band minimum (CBM) orbitals with X=Cl, Br, or I …”
Section: Optical Propertiesmentioning
confidence: 99%
“…[32,39,48] Thesev alues come from the energy difference between (Pb)6s(X)np valence band maximum (VBM) and (Pb)6p conduction band minimum (CBM)orbitals with X = Cl, Br, or I. [64,65] Theb andgap energy can be tuned from 1.6t o2 .3 eV by the changing the I/Br ratio [48,66] (Figure 3a)a nd also from 2.3 to 3.1 eV by controlling the Cl/Br ratio. [32,67] Overall, by changing the halide ratio,t he bandgap energy can be tuned from 3.1 (UV) to 1.6 eV (NIR).…”
Section: Tuning Optical Bandgap In Mixed-halide Perovskitesmentioning
confidence: 99%
“…The calculated results revealed that the conduction band minima and valance band maxima are located at the R high symmetry points, hence evidenced for the direct band gap semiconductors. The calculated band gaps by both potentials (GGA and mBJ) are listed in the table 2, from where it can be seen that the band gaps calculated with mBJ have been improved as compared to other theoretical results reported in literature but lower than to experimental values which is due the limitations and under estimations of GGA [26,27]. Direct band gap can also be detected at other symmetry points (M, G and X).…”
Section: Electronic Propertiesmentioning
confidence: 79%
“…MAPbCl 3 , MAPbBr 3 , and MAPbI 3 have bandgap energies of 3.11, 2.3, and 1.55 eV, respectively . These bandgaps correspond to the energy difference between (Pb)6s(X)np valence band maximum (VBM) and (Pb)6p conduction band minimum (CBM) …”
Section: Optical Properties Of Pvk Platelets and Wiresmentioning
confidence: 99%